1982
DOI: 10.1056/nejm198210073071501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HLA-A and HLA-B Matching on Survival of Grafts and Recipients after Renal Transplantation

Abstract: Data on the effect of HLA-A and HLA-B matching between unrelated donors and recipients focus mainly on graft survival. After linking the follow-up data of the European Dialysis and Transplant Association and those of the Eurotransplant Foundation, the effect of HLA-A and HLA-B matching on recipient survival could be studied. Recipients of well-matched kidneys--i.e., without mismatches for the HLA-A and B antigens--had 51 per cent graft survival at five years, whereas recipients of grafts mismatched for four an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 11 publications
1
11
1
Order By: Relevance
“…N ational and international renal transplant registries show that matching for human leukocyte antigen (HLA) remains an important determinant of long-term graft and patient survival (1)(2)(3)(4)(5). Organ allocation algorithms for cadaveric donor kidneys are often designed to promote equity of access to transplantation but most algorithms also incorporate matching for HLA in an attempt to maximize transplant outcome (6 -8).…”
mentioning
confidence: 99%
“…N ational and international renal transplant registries show that matching for human leukocyte antigen (HLA) remains an important determinant of long-term graft and patient survival (1)(2)(3)(4)(5). Organ allocation algorithms for cadaveric donor kidneys are often designed to promote equity of access to transplantation but most algorithms also incorporate matching for HLA in an attempt to maximize transplant outcome (6 -8).…”
mentioning
confidence: 99%
“…H uman leukocyte antigen (HLA) matching has a beneficial effect on kidney transplant outcome and limiting the number of mismatches at HLA-A, -B, and -DR is an integral component of national organ allocation policies (1)(2)(3)(4)(5)(6). Conventional HLA-matching algorithms are based on several mismatches at each HLA locus, but a potential drawback of this approach is that all mismatches within a given locus are assigned equal weighting, regardless of structural or aminoacid sequence differences between donor and recipient HLA types.…”
mentioning
confidence: 99%
“…Traditionally, high degree of HLA mismatching was associated with higher rejection rates and worse graft survival. 11,12 In the setting of modern immunosuppressant medications, such as lymphocyte depleting agents and calcineurin inhibitor-based maintenance therapies, the paradigm has shifted, and studies have demonstrated excellent long-term graft outcomes independent of the degree of HLA mismatching. 13 Our data suggest, however, that greater HLA mismatching significantly amplifies the risk for graft loss among HIV-infected KT recipients, in particular the subset that are co-infected with HCV.…”
Section: Discussionmentioning
confidence: 99%